The Effects of E-Module with Guided Discovery Model on Students Learning Outcomes in Electrolyte and Nonelectrolyte Solution - Sakinah, Mutiara; Yerimadesi, Yerimadesi (Jurnal Pendidikan MIPA, 2022)
This study aims to analyze the effect of using an e-module electrolyte and nonelectrolyte solution based on guided discovery learning on student learning outcomes. This quasi-experimental study used a randomized control-group pretest-posttest design. The population consisted of grade X student of SMA Negeri 1 Padangpanjang in the 2021/2022 school year and samples were taken using simple random sampling technique. The research instrument was a multiple-choice test and the data were analyzed by n-gain test and hypothesis testing by t-test. Based on data analysis, n-gain experimental class is higher than the control class with a medium category and the hyphothesis is the use of an e-module electrolyte and nonelectrolyte solution based on guided discovery learning is effect in improving student learning outcomes at SMA Negeri 1 Padangpanjang. Keywords: e-module, guided discovery model, learning outcomes. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp496-504